Evaluation of bactericidal activity of Hannon honey on slowly growing bacteria in the chemostat - Sufya, Najib (Dove Medical Press, 2014)
There is renewed interest in the therapeutic use of honey, including use in the treatment of infected wounds and burn patients. In this study, we have assessed the antibacterial activity of Libyan floral Hannon honey on Escherichia coli and Staphylococcus aureus, both known to infect wounds. The effects of four concentrations (5%–30%) of honey were compared with that of four antibiotics (ampicillin, tetracycline, polymyxin, and ciprofloxacin) on the growth of these bacteria at early log, mid log, and late log phases. It has been shown that E. coli and S. aureus are to some degree susceptible during mid log phase compared with late log phase, demonstrated by their complete resistance to antibiotics. Chemostat culture was used to investigate the effect of honey on E. coli grown at a steady state with specific growth rates between 0.1 to 0.5 hour(−1). The rate of killing was distinctively clear during the two stages of growth monitored: there was a relatively moderate reduction at the slow growth phase (0.1 to 0.3 hour(−1)), while a dramatic reduction was obtained at the fast growth phase (0.3 to 0.5 hour(−1)), reaching a complete reduction at 0.5 hour(−1). These results complement data using the cup-cut technique. The antibacterial effect of honey was concentration and time dependent, the bactericidal effect was indeed observed at low concentrations, it demonstrates that the honey has more impact on slow growing bacteria than antibiotics have. We suggest that more reduction could be achieved at higher concentrations of honey. These results may have important clinical implications, such as for the management of wound and burn patients.